Comparative study of urban residential design and microclimate characteristics based on ENVI-met simulation. Issue 9 (November 2019) - Wang, Yanfei; Zhou, Dian; Wang, Yibo; Fang, Yan; Yuan, Yousheng; Lv, Liang
This study assesses the urban microclimate characteristics that influence typical urban residential districts in relation to district planning and design. This study uses the ENVI-met numerical simulation technology to compare differences in microclimate characteristics of five residential districts in the city of Luoyang, China. A similar residential scale was used for the simulation of these districts, but with different architectural designs and space layouts. Based on the simulation and with the same environmental and climatic conditions, the architectural planning and layout of residential areas – building heights, building densities, greening and water surface areas and pavements – were shown to have important impacts on the microclimate characteristics of the environment. The variations of simulated and measured temperatures were parabolic in shape, and the variation trends of both were similar. The relative humidity in a residential district was shown to decline with an increase in temperature. The increase in height of taller high-rise buildings can pose a corresponding increase in wind speed in neighbourhood districts.